A review of adaptive overcurrent protection in distribution networks with integration of distributed energy resources - Nur Aisyah Mohd Yusof; Zaipatimah Ali; Mohd Zainal Abidin Ab Kadir (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents a review of an adaptive overcurrent protection scheme in a distribution network with the integration of distributed energy resources. The rapid integration of distributed energy resources brings challenges to the existing overcurrent protection system. The impacts are change in fault current magnitude and direction of current flow from radial to the multi-source dynamic network, which causes changes in network topology, inaccurate fault detection, and loss of coordination among protection systems. In this paper, the solution identified for reliable operation of overcurrent protection in the distribution network are network topology estimation, fault detection, and adaptive coordination.